The economical management of farm lands - Reed, Hiram R. (My University, 1907)
Introduction: At this age of rapidly increasing habitation of the world it is evident that there will eventually be a time when land for the occupation of the population will be in much greater demand than at present, and as farmers will necessarily constitute a large proportion of the population it is important that the lands occupied by them, be economically managed. The time will come when farmers cannot all have as many acres as has been possible for them to have in the past. All of the good farming land has or will soon be occupied and the time is past when farmers in the East can abadon their farms, go to the West and have land for the asking in such large quantities that it is nnnecessary and unprofitable to give much consideration to its management. A few years ago only the land which was most valuable and which could be conveniently farmed was used for that purpose, but in the future most or all lands must be occupied and instead of taking a farm of large area and farming it in a wasteful way, the farmer will farm small areas and give especial attention to the economical management of the land, thus deriving as much or greater profit than would be derived from farms comprising more but less economically handled land.
Citation: Reed, Hiram R. The economical management of farm lands. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Farm Land; Agricultural Management; Agricultural Economics; Theses